Think Unique: Perceptions of Uniqueness Increases Resistance to Persuasion and Attitude-Intention Relations - Blankenship, Kevin L.; Kane, Kelly A.; Machacek, Marielle G. (Frontiers in Psychology, 2021)
The present research examines whether the perceived uniqueness of one’s thoughts and salience of uniqueness motivations can influence attitude strength and resistance. Participants who rated their thoughts as relatively unique formed attitudes that showed greater correspondence with behavioral intentions to act on the attitude (Study 1). In Study 2, participants who recalled a previous purchase motivated by the desire to be unique (versus to fit in) after generating message counterarguments were less persuaded (more resistant) and reported greater willingness to act on their (negative) attitude. Moreover, attitudes mediated the effect of the purchase manipulation on intentions to act on the attitude.